2009
DOI: 10.1096/fj.09-142281
|View full text |Cite
|
Sign up to set email alerts
|

Control of oxidative phosphorylation by vitamin A illuminates a fundamental role in mitochondrial energy homoeostasis

Abstract: The physiology of two metabolites of vitamin A is understood in substantial detail: retinaldehyde functions as the universal chromophore in the vertebrate and invertebrate eye; retinoic acid regulates a set of vertebrate transcription factors, the retinoic acid receptor superfamily. The third member of this retinoid triumvirate is retinol. While functioning as the precursor of retinaldehyde and retinoic acid, a growing body of evidence suggests a far more fundamental role for retinol in signal transduction. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 48 publications
3
78
0
Order By: Relevance
“…However, our study has some limitations. We evaluated important mechanisms associated with abnormal alveolar development (oxidative stress, angiogenesis, cytokines, chemokines, growth factors, and extracellular matrix), but retinoids may affect multiple pathways simultaneously, including those that were not evaluated in this study (1,17,39,47). Experiments using whole lung homogenates do not permit the identification of changes in gene expression or protein synthesis in selected cell populations in vivo, such as airway epithelia, endothelial VARA, 10:1 molar combination of vitamin A (the nutrient) and all-trans retinoic acid (the metabolite); n ϭ 3 mice/group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study has some limitations. We evaluated important mechanisms associated with abnormal alveolar development (oxidative stress, angiogenesis, cytokines, chemokines, growth factors, and extracellular matrix), but retinoids may affect multiple pathways simultaneously, including those that were not evaluated in this study (1,17,39,47). Experiments using whole lung homogenates do not permit the identification of changes in gene expression or protein synthesis in selected cell populations in vivo, such as airway epithelia, endothelial VARA, 10:1 molar combination of vitamin A (the nutrient) and all-trans retinoic acid (the metabolite); n ϭ 3 mice/group.…”
Section: Discussionmentioning
confidence: 99%
“…Veness-Meehan et al (46) demonstrated that RA treatment of newborn rats improves survival and alveolarization during hyperoxia exposure. The exact mechanisms by which RA attenuates hyperoxia effects in the newborn lung are uncertain, but RA is known to modulate oxidative stress mediators (1,24), proinflammatory mediators (26), and growth factor expression (39), and such mechanisms may be involved in our model. Regardless of the mechanism by which retinoids exert their effect, an increase in lung VA is essential for this benefit.…”
Section: Discussionmentioning
confidence: 99%
“…2, 4, 5). Protein modification by retinol 38) or mitochondrial energy homoeostasis, 39) could be one mechanism employed by retinol to affect cancer cells. Currently, elucidation of the mechanisms of retinol's actions, which are distinct and depend on cell type or experimental methods (activity, mRNA or protein expression etc.)…”
Section: Discussionmentioning
confidence: 99%
“…It was observed both in cell cultures and animal models [10,52] that retinol-induced oxidative stress is caused by the administration of concentrations above the reported physiological limit, which would increase the availability of this molecule to take part in oxidation-reduction cycles inside cells. On the other hand, it was recently reported that retinol is able to induce the mitochondrial activity by enhancing pyruvate dehydrogenase activity through a nongenomic mechanism of PKC activation, thus resulting in increased free radical formation [53] . This would explain why increased concentrations of retinol induce reactive species production in both cell cultures and animal models.…”
Section: Discussionmentioning
confidence: 99%